The hybridization of management systems in South African development NGOs : A view from the South - Antere, Tuulikki (My University, 2019)
Development aid has gained increasing prominence in the public debate, but research on its management has remained relatively scarce. In addition, what has been largely ignored is the voice of the donee party. Using postcolonial theory as a framework, the current thesis takes a cross-disciplinary approach on the matter. The purpose is to contribute to the discussion from an NGO management perspective, examining from the locals’ point of view what determines the type of management sys-tems in use in Western-funded South African NGOs. Using multiple case study as a research design, the data was collected interviewing local NGO managers in South Africa and subsequently analysed thematically. It was found that the size of both the donor and the donee organisations, the relationship with the donor, context dynamics, modern Western business-principles as well as global trends have a role to play in the hybridization of management systems in Western-funded South African NGOs. The contribution of the current thesis is to provide a framework of NGO management from the point of view of the Global South, in order to generate ideas for enhanced practice. Further, it serves to create awareness of the unequal power dynamics between the donor and the donee in order for the interaction to be more equal in the future.

Kehitysyhteistyö on saanut enenevässä määrin jalansijaa julkisessa keskustelussa, mutta sen johtamiseen keskittynyt tutkimus on jäänyt verrattain vähäiseksi. Keskustelua on käyty laajalti länsimaisesta näkökulmasta käsin, jolloin kehitysyhteistyön kumppanijärjestöjen ääni on helposti jäänyt kuulumattomiin. Tämä tutkielma lähestyy aihetta poikkitieteellisesti käyttäen postkolonialistista teoriaa viitekehyksenä. Tarkoitus on osallistua keskusteluun NGO-johtamisen näkökulmasta ja tarkastella paikallisten ääntä kuunnellen, mikä määrittää minkälaisia johtamisjärjestelmiä käytetään suomalaisrahoitteisissa etelä-afrikkalaisissa kehitysyhteistyöjärjestöissä. Tutkielma on suunniteltu monitapaustutkimuksen mukaisesti. Aineisto on kerätty haastattelemalla etelä-afrikkalaisia NGO-johtajia ja analysoitu temaattisesti. Analyysi osoittaa, että rahoitettavan sekä rahoittajaorganisaation koko, rahoittajasuhteet, kontekstidynamiikka, länsimaiset liikkeenjohdolliset periaatteet sekä globaalit trendit ovat osallisia suomalaisrahoitteisten etelä-afrikkalaisten kehitysyhteistyöjärjestöjen johtamisjärjestelmien hybridisaatioprosessissa. Tutkielma tarjoaa uudenlaisen viitekehyksen NGO-johtamiseen globaalin etelän näkökulmasta johtamiskäytäntöjen parantamiseksi. Lisäksi se herättelee tunnistamaan rahoittajan ja rahoitettavan välistä epätasa-arvoista valtasuhdetta, jotta siihen huomiota kiinnittämällä voisi sitä tulevaisuudessa muuttaa.
Keywords: management, NGO, management systems, postcolonialism, South Africa